All this could be yours [compact disc, unabridged] - Attenberg, Jami (Houghton Mifflin Harcourt, 2019)
Now that her power-hungry father Victor is on his deathbed, Alex travels to New Orleans to unearth the secrets of who Victor is and what he did over the course of his life and career.